Study on FTTx-Oriented VDSL2 Vectoring Technology and Application - Haolin Li; Ming Jiang; Chengbin Shen; Bo Wang (Dianxin kexue)
VDSL2 vectoring and G.inp technologies and their progress were investigated. Based on the results of laboratory and field testing, VDSL2 vectoring and G.inp's functionalities, performance and interoperability were evaluated in detail. Combined with the status of telecom operators' networks construction and maintenance, VDSL2 vectoring and G.inp's deployment mode and equipment requirements in FTTx+VDSL2 scenario were proposed. Finally, development trend of VDSL2 vectoring and G.inp technologies and their application were given.